Електронне урядування в Україні: нові можливості, старі опоненти - Яковлев, Денис (Видавництво Львівської політехніки, 2012)
The article deals with e-government in the context of current debates about the nature, functions and prospects of governance and public policy in the context of globalization and informatization and conditions and dimensions of the implementation of policy and outlines the development of e-government in this respect. Consideration of the perspectives associated with the formation of e-government in Ukraine, can not be limited to finding innovations in technological support of the public sector. E-government advocates are not a means of transferring documents from paper to electronic, but the phenomenon is deeply related to public policy: it is "more governmental than digital".
Keywords: демократія; урядування; електронна демократія; публічна політика; політичні комунікації; політичні рішення